Effects of Ai Chi and Yamamoto new scalp acupuncture on chronic low back pain - Bárbara Maria Camilotti; Neiva Leite; Daysi Alberti; Inara Aparecida Francisco; Vera Lúcia Israel
Abstract Introduction : Low Back pain affects a large part of the population and represents a major socioeconomic problem. There are many resources for treatment of this symptom, among them: acupuncture and aquatic therapy. Objective : To compare the effects of an aquatic physical therapy program (AI CHI) and Yamamoto New Scalp Acupuncture (YNSA) in pain intensity and functionality in patients with chronic low back pain. Material and methods : a clinical trial with a randomized sample. Sixty six individuals with chronic low back pain, of both genders were selected, however 44 individuals completed the study. The individuals were divided into three groups AI CHI (n = 15), YNSA (n = 15) and Control (n = 14). Ten 10 interventions with a program of aquatic therapy method (Ai Chi) and Yamamoto New Scalp Acupuncture (YNSA), were made, twice a week. The control group received the intervention only after the end of the study. Pain intensity was assessed by a visual analogue scale (VAS) and the functional capacity by Owestry functionality Index. Results : There was significant reduction in pain and improvement in functional capacity (p < 0.05) in YNSA and AI CHI and when compared to the control group. Conclusion : It was concluded that the YNSA and AI CHI were effective in reducing pain and improving the functionality of the lumbar spine in patients with chronic low back pain.